Management of the loss reserve accrual and the distribution of earnings in the property-casualty insurance industry - Beaver, William H.; McNichols, Maureen F.; Nelson, Karen K. (Journal of Accounting and Economics, 2003)
We document that property-casualty insurers with small positive earnings understate loss reserves relative to insurers with small negative earnings. Furthermore, loss reserves are managed across the entire distribution of earnings, with the most income-increasing reserve accruals reported by small profit firms, and the most income-decreasing reserve accruals reported by firms with the highest earnings. We analyze this pattern separately for public, private, and mutual companies, and find that public companies and mutuals manage loss reserves to avoid losses, but that private companies do not. We also find evidence of reserve management to avoid losses by financially healthy and distressed firms.